Performance of streaked bean genotypes (Phaseolus vulgaris L.) in a low-altitude "cerrado" region - Brito, Wendylla Dark de Paula; Buzo, Fernando de Souza; Santos, Diogo dos; Barros, Bruna da Silva; Sales, Letícia Zylmennith de Souza; Ito, Marcio Akita; Arf, Orivaldo; Mello, Leonardo Cunha (Seven Editora, 2024)
The study aimed to evaluate different genotypes of speackled beans in comparison with established cultivars through the Cultivation and Use Value Trial. The research, conduced in collaboration with with EMBRAPA – Rice and Beans, took place in an experimental area characterized by typical Dystrophic RED Oxisol soil. (EMBRAPA, 2018). The average annual precipitation is 1,370 mm, the average annual temperature is 74.3ºF and the relative humidity is between 70 and 80%. Planting was carried out in April/May 2022. The experimental design was randomized complete block, with 12 treatments, consisting of different speackled beans genotypes, each with three replications. The genotypes used were: CNFRJ 17783, BRS FS311; CNFRJ 17774, BRSMG REALCE; CNFRJ 17778; CNFRJ 18239; CNFRJ 18237; CNFRJ 18222; CNFRJ 17792; CNFRJ 18217; CNFRJ 17548; CNFRJ 17545. Experimental plots consisted of four rows, each 4 meters in lenght, with inter-row spacing of 0.45 meters. The following evaluations were performed: plant population; flowering and cycle duration; number of pods per plant; number of grains per plant; number of grains per pod; 100-grains wight; and grain yield. "The genotype CNFRJ 17783 exhibited excellent performance across all variables, particularly noteworthy for its superior grain productivity. The highest yields were observed in genotypes CNFRJ17783, CNFRJ17545, CNFRJ18239, and CNFRJ18217, indicating efficiency in crop yield. Based on these results, the genotype CNFRJ 17783 may be recommended for the Cerrado region as a new cultivar. DOI:https://doi.org/10.56238/sevened2023.006-109